Targum and Testament revisited Aramaic paraphrases of the Hebrew Bible ; a light on the New Testament - McNamara, Martin 1930- (Grand Rapids, Mich. [u.a.] Eerdmans, 2010)
Development of doctrine in Judaism -- The synagogue and synagogue worship -- Aramaic as the language of the Jews -- Early written targums -- Some characteristics of targumic renderings -- Origin and transmission of the Palestinian targum -- Date of the Palestinian targum -- Reverential manner of speaking of God -- God and creation -- The Holy Spirit -- Father in Heaven -- Sin and virtue -- Eschatology -- The targums and Johannine literature -- Other passages and concluding remarks -- Targums of the Pentateuch -- Geography of the Palestinian targums of the Pentateuch -- Targums of the prophets -- Targums of the hagiographa -- Appendix : the Aramaic Bible project
Development of doctrine in Judaism -- The synagogue and synagogue worship -- Aramaic as the language of the Jews -- Early written targums -- Some characteristics of targumic renderings -- Origin and transmission of the Palestinian targum -- Date of the Palestinian targum -- Reverential manner of speaking of God -- God and creation -- The Holy Spirit -- Father in Heaven -- Sin and virtue -- Eschatology -- The targums and Johannine literature -- Other passages and concluding remarks -- Targums of the Pentateuch -- Geography of the Palestinian targums of the Pentateuch -- Targums of the prophets -- Targums of the hagiographa -- Appendix : the Aramaic Bible project.
Includes bibliographical references and indexes
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Bible -- Versions, Palestinian; Bible -- Relation to the Old Testament